If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1c + 2 = -6c + -13 Reorder the terms: 2 + -1c = -6c + -13 Reorder the terms: 2 + -1c = -13 + -6c Solving 2 + -1c = -13 + -6c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '6c' to each side of the equation. 2 + -1c + 6c = -13 + -6c + 6c Combine like terms: -1c + 6c = 5c 2 + 5c = -13 + -6c + 6c Combine like terms: -6c + 6c = 0 2 + 5c = -13 + 0 2 + 5c = -13 Add '-2' to each side of the equation. 2 + -2 + 5c = -13 + -2 Combine like terms: 2 + -2 = 0 0 + 5c = -13 + -2 5c = -13 + -2 Combine like terms: -13 + -2 = -15 5c = -15 Divide each side by '5'. c = -3 Simplifying c = -3
| 654/15 | | -2w+1=-7w+41 | | 5h=3x+150 | | -2f-6=-5f-3 | | 11d+5=3d-3 | | 7z-6=3z+4 | | -8k+4=-6k+20 | | 9j-4=5j+28 | | -6u+7=u+70 | | y/5=-20 | | 11u+1=6u-29 | | -x-4=-4x+2 | | -8g+7=-g+63 | | 70=6x-14 | | 7j-4=3j-28 | | 10e-4=4e-10 | | 2a+4=-3a-36 | | -2q+6=3q-24 | | 2x-1=-x-28 | | 6h-4=h-9 | | 9y-1=5y+15 | | 12+8=5d+57 | | 7(3g+8)/4=35 | | 8-32x+27x-3=0 | | 4(x-5)=-1.6 | | 12d+8=8d+16 | | 13=5c-9 | | 9e-7=28.1 | | 8(x-2)=26.4 | | 2(3y-6)=-18 | | 2(7v-4)=-22 | | 3(4k-4)=60 |